Proton Irradiation Effects on the Pyroelectric Properties of P‐Type Bismuth Antimonide/Poly(vinylidene fluoride–trifluoroethylene) Composite Films - Cai, Chuanyang; Zhang, Hong; Li, Bo; Han, Zhijia; Wang, Fang; Hou, Pengfei; Liu, Weishu (Advanced electronic materials, 2023)
Organic pyroelectric materials are widely applied as temperature sensors in wearable electronic devices due to their good biocompatibility and stability. Real‐time monitoring of the physiological state of the human body requires pyroelectric materials with a fast response time and large output voltage. In this study, the pyroelectric characteristics of poly(vinylidene fluoride–trifluoroethylene) (P(VDF–TrFE)) films are improved with the use of commercial inorganic P‐type bismuth antimonide (P‐Bi2Te3) fillers. Composite films with 0.2 wt% P‐Bi2Te3 increase the pyroelectric response time and voltage by improving the thermal diffusivity and enhancing the β‐phase content, respectively. Proton irradiation results in further improvement of the pyroelectric response time from 22 to 0.5 s. The proton irradiation‐induced ionization energy loss improves the conductivity of the composite films, thereby enhancing the pyroelectric response time. These results show that P‐Bi2Te3 doping is beneficial for improving the pyroelectric properties of P(VDF–TrFE) and that proton irradiation is an effective method for further improving the response time of inorganic–organic composite films. The pyroelectric characteristics of poly(vinylidene fluoride–trifluoroethylene) films are improved with the use of inorganic P‐type bismuth antimonide (P–Bi2Te3) fillers. Composite films with 0.2 wt% P‐Bi2Te3 increase the pyroelectric response and voltage by improving the thermal diffusivity and enhancing the β‐phase content, respectively. Proton irradiation results in further improvement of the pyroelectric response time from 22 to 0.5 s.